Homeschooling Learning Management In Fostering Student CharacterIn South Tangerang City - Martadihardja, Anwar; Hanafiah, Hanafiah; Karim Fatkhullah, Faiz (CV. Inara, 2022)
This research specifically aims to get an overview and analysis of planning, organizing, implementing, evaluating, constraining, and solving homeschooling learning in fostering student character at Homeschooling Kak Seto and Homeschooling Technosa South Tangerang. This research uses management theory from Terry and character theory from Lickona. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews and documentation studies. The results of the study indicate that in planning the teacher prepares a Character Learning Implementation Plan referring to the Syllabus. Organizing is still constrained by the human resource management system in supporting the creation of learning in homeschooling as a whole. In the implementation process, the teacher carries out the learning process in accordance with the steps contained in the Learning Implementation Plan; Assessment is carried out by teachers through two types, namely process assessment and learning outcomes assessment. Constraints encountered include (a) Limited time allocation for Citizenship Education learning, (b) There is a dissonance between education at home and education applied in homeschooling, Solutions used to overcome obstacles (a) Fortify students and all elements in homeschooling with noble character, character, and positive character through well-programmed habituation and exemplary activities (b) Developing a typical homeschooling curriculum as the basis for education of identity and religious character. The conclusion of this research is that good civics education learning governance can develop the character of homeschooling students.